The emerging power and promise of non-coding RNAs in chronic pain - Zhang, Changteng; Gao, Rui; Zhou, Ruihao; Chen, Hai; Liu, Changliang; Zhu, Tao; Chen, Chan (Frontiers in Molecular Neuroscience, 2022)
Chronic pain is an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage lasting longer than 3 months. Chronic pain is the main reason why people seek medical care and exerts an enormous economic burden. Genome-wide expression analysis has revealed that diverse essential genetic elements are altered in chronic pain patients. Although many possible mechanisms of chronic pain have been revealed, we are still unable to meet all the analgesic needs of patients. In recent years, non-coding RNAs have been shown to play essential roles in peripheral neuropathy and axon regeneration, which is associated with chronic pain occurrence and development. Multiple key ncRNAs have been identified in animal models of CP, such as microRNA-30c-5p, ciRS-7 and lncRNA MRAK009713 etc. This review highlights different kinds of non-coding RNAs in the regulation of chronic pain, which provides a more comprehensive understanding of the pathogenesis of the disease. It mainly focuses on the contributions of miRNAs, circRNAs and lncRNAs to chronic pain, specifically peripheral neuropathic pain, diabetic neuropathic pain, central neuropathic pain associated with spinal cord injury, complex regional pain syndrome, inflammatory pain and cancer-induced pain. In addition, we summarize some potential non-coding RNAs as novel biomarkers for chronic pain and its complications. With an in-depth understanding of the mechanism of chronic pain, non-coding RNAs may provide novel insight into chronic pain and could become new therapeutic targets in the future.